Integrated Urban System and Energy Consumption Model: Residential Buildings - Papa, Rocco; Gargiulo, Carmela; Carpentieri, Gerardo (TeMA - Journal of Land Use, Mobility and Environment, 2014)
This paper describes a segment of research conducted within the project PON 04a2_E Smart Energy Master for the energetic government of the territory conducted by the Department of Civil, Architectural and Environment Engineering, University of Naples "Federico II". In particular, this article is part of the study carried out for the definition of the comprehension/interpretation model that correlates buildings, city’s activities and users’ behaviour in order to promote energy savings. In detail, this segment of the research wants to define the residential variables to be used in the model. For this purpose a knowledge framework at international level has been defined, to estimate the energy requirements of residential buildings and the identification of a set of parameters, whose variation has a significant influence on the energy consumption of residential buildings.